2023
DOI: 10.3390/biomedicines11061517
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 Blockade Diminishes Intratumoral Macrophage Recruitment and Augments Survival of Syngeneic Pancreatic Cancer-Bearing Mice

Abstract: Pancreatic cancer is known for its tumor microenvironment (TME), which is rich in stromal and immune cells supporting cancer growth and therapy resistance. In particular, tumor-associated macrophages (TAMs) are known for their angiogenesis- and metastasis-promoting properties, which lead to the failure of conventional therapies for pancreatic cancer. Hence, treatment options targeting TAMs are needed. The C-C chemokine receptor type 4 (CCR4) is critical for immune cell recruitment into the TME, and in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Besides CCR2, CCR4 is a receptor expressed on monocytes/macrophages that promotes their migration [ 45 , 46 ]. The CCL2/CCR4 axis plays a role as a chemoattractant of monocytes/macrophages in pancreatic ductal carcinoma (PDA) and in murine pancreatic cancer [ 47 , 48 , 49 ]. Therefore, it is a potential immunological target to suppress TAM formation; in fact, CCR4 blockade improves prognosis in pancreatic cancer [ 48 ].…”
Section: Recruitment Of Monocytes/macrophages Into Tumorsmentioning
confidence: 99%
“…Besides CCR2, CCR4 is a receptor expressed on monocytes/macrophages that promotes their migration [ 45 , 46 ]. The CCL2/CCR4 axis plays a role as a chemoattractant of monocytes/macrophages in pancreatic ductal carcinoma (PDA) and in murine pancreatic cancer [ 47 , 48 , 49 ]. Therefore, it is a potential immunological target to suppress TAM formation; in fact, CCR4 blockade improves prognosis in pancreatic cancer [ 48 ].…”
Section: Recruitment Of Monocytes/macrophages Into Tumorsmentioning
confidence: 99%
“…In vitro experiments showed that employing an anti-CCR4 antibody effectively decreased Treg cell counts, facilitating the activation of cancer/testis antigen-specific T cell responses [ 75 ]. Blocking CCR4 reduces the infiltration of TAMs and enhances survival in a syngeneic mouse model of pancreatic cancer [ 76 ]. CCL22 might serve as a promising biomarker of poor prognosis in cancer [ 77 ].…”
Section: Ccl22mentioning
confidence: 99%